Shenhuang Granules for patients with sepsis: study protocol of a multicenter, randomized, double-blind, placebo-controlled clinical trial - Shen, Meng-Yuan; Li, Ze-Jiong; Feng, Dan-Dan; Yang, Dong-Dong; Liu, Shan; Fu, Yi-Heng; Fang, Bang-Jiang; Wu, Jian-Nong (Frontiers in Medicine, 2025)
BackgroundSepsis is a life-threatening condition characterized by organ dysfunction due to a dysregulated host response to infection, with a persistently high mortality rate. In recent years, the role of Traditional Chinese Medicine in treating sepsis has gained recognition both domestically and internationally. Shenhuang Granules (SHG), composed of six ingredients: Panax ginseng C.A.Mey. (Ginseng Radix et Rhizoma), Rheum palmatum L. (Rhei Radix et Rhizoma), Sargentodoxa cuneata (Oliv.) Rehder & E.H.Wilson (Sargentodoxae Caulis), Taraxacum mongolicum Hand.-Mazz. (Taraxaci Herba), Aconitum carmichaelii Debeaux (Aconiti Lateralis Radix Praeparata), and Whitmania pigra (Whitman, 1884) (Hirudo), has been reported to strengthen and consolidate vital energy, clear heat and detoxify, promote qi circulation and gastrointestinal function, and enhance blood circulation. This study aims to evaluate the clinical efficacy and safety of SHG in patients with sepsis.Methods and analysisA multicenter, randomized, double-blind, placebo-controlled clinical trial will be conducted and will enroll 410 patients aged ≥ 18 years who meet the diagnostic criteria of Sepsis 3.0. Participants will be randomly assigned in a 1:1 ratio to either the SHG group or the placebo group via a central randomization system. The SHG group will receive 7 days of standard sepsis bundle management combined with SHG, while the placebo group will receive the same management with a placebo for 7 days. Each dose will be dissolved in 100 mL of warm water (approximately 40 °C) and administered twice daily either orally or via a feeding tube (gastric or intestinal). The primary endpoint was 28-day all-cause mortality. Secondary endpoints include 28-day cumulative mechanical ventilation-free days, APACHE II score, SOFA score, overall mortality rate, total hospital stay, hospitalization cost, and inflammatory factors. Adverse events will be recorded throughout the study period.DiscussionThis trial represents the first multi-center randomized controlled study in China evaluating the effect of SHG on patients with sepsis. The findings are expected to provide robust evidence regarding the efficacy and safety of SHG in sepsis management, offering evidence-based recommendations for clinical practice.Clinical trial registrationThe study was registered on September 21, 2024, with the identifier number NCT06514339.